Profit, Politic, and Ecological Discourse: a Capitalist Environmental Value in Crichton’s State of Fear - Safana, Iftinan Rose Putri (British (Jurnal Bahasa dan Sastra Inggris), 2025)
This research critically examines how capitalist environmental values, characterized by profit-driven conservation, political manipulation, and market commodification, are represented in Michael Crichton’s State of Fear. Moreover, this study extends Stern and Dietz’s foundational environmental values framework by introducing new categories that reflect the complexities of environmental discourse in contemporary capitalist societies, providing a nuanced understanding of how ecological concerns are intertwined with economic and political interests. This research uses a qualitative approach based on textual data from the novel State of Fear. Then, the data was analyzed using close reading techniques to find indicators of capitalist environmental values, which were then interpreted using environmental value theory, green capitalism, and classical capitalism. The results of this research show that capitalist environmental values can be expressed through three things. The first is profit-driven conservation, which shows that environmental conservation is carried out only based on economic benefits. The second is the use of political and religious power to obscure the exploitation of the environment and society and build a positive image. The last is the creation and mystification of markets, which reflects how environmental issues are transformed into markets and give rise to products that seem to support environmental morality and build an image that disguises environmental damage.Keywords: Capitalist Environmental Value; Capitalism; Profit, Politics; Ecological Discourse